A Framework for Managing Government Guarantees - Razlog, Lilia; Irwin, Tim; Marrison, Chris (World Bank, Washington, DC, 2020)
Managing government debt guarantees is difficult because the potential costs of guarantees are hard to estimate and typically do not show up in the reported budget deficit. A good framework for managing guarantees can, however, help governments overcome the difficulty and enhance the transparency of guarantees. This paper sets out a checklist of issues for a government to consider when designing or revisiting its framework for managing guarantees. The checklist comprises: (1) steps to establish macroeconomic control over guarantees by setting limits on their use and restricting the authorization to grant them; (2) steps to improve decisions to grant individual guarantees by means of guidelines, restrictions, conditions, cost estimation, guarantees fees, and a structured process for making the decisions; and (3) steps to ensure careful management after the granting of guarantees, including the recording and reporting of guarantees, arrangements to pay when necessary, and learning from past experience.